Public Lecture: Pieces Back Together: Community Memory of Sexual Violence in Radical Environmental Organizations in the Pacific Northwest of USA - (CPCC), Policy Studies on Culture & CMNS (Stream: Interdisciplinary Journal of Communication, 2015)
A CPCC public lecture on the topic of "Community Memory of Sexual Violence in Radical Environmental Organizations in the Pacific Northwest of USA" will be hosted on November 19, 2015 from 7:30 - 9 pm in room HC 7000 (SFU Vancouver). The event is sponsored by FCAT’s Centre for Policy Studies on Culture & Communities. Please see the attached PDF for further details.